Dramaturgi Praktik Lingkungan Pembuatan Profil Ekowisata Berbasis Teknologi Drone Padukuhan Bleberan Kabupaten Kulonprogo D.I. Yogyakarta - Yudiaryani Yudiaryani; Pius Rino Pungkiawan; Bunga Islamy (Dance and Theatre Review, 2025)
Environmental Dramaturgical Practice for Ecotourism Profiling Based on Drone Technology in Bleberan Hamlet, Kulonprogo Regency, Yogyakarta Special RegionThis article examines ecological dramaturgical practice through drone-based performative mapping within the context of ecotourism and communitybased cultural performance. Responding to conditions of twenty-firstcentury media abundance, dramaturgy is reconceptualised from a predominantly analytical framework into an expanded, practice-based methodology operating across ecological, spatial, and digital domains. This study positions drone technology not merely as a visual documentation tool, but as an intermedial dramaturgical agent that actively shapes relationships between bodies, landscapes, technologies, and communities. Drawing on a case study in Padukuhan Bleberan, Kulon Progo, the research demonstrates how ecotourism functions as a performative practice that integrates ecological landscapes, ritual spaces, cultural memory, and local creative economies into a digital mapping system. Drone-based visual profiling produces performative archives that extend cultural practices beyond live events, enhancing visibility, accessibility, and sustainability. Methodologically, the study combines dramaturgical practice, ecological performance perspectives, and digital media analysis, supported by field observation, interviews, and collaborative evaluation with the local community. This approach contributes to contemporary discussions on ecodramaturgy, intermedial performance, and community-based spatial practice.Keywords: dramaturgical practice; ecological dramaturgy; performative mapping; drone technology; ecotourismKata kunci: ekowisata; teknologi drone; model profil; dukuh Bleberan.